Three-step iterations for mixed quasi variational-like inequalities - Muhammad Aslam Noor (International Journal of Mathematics and Mathematical Sciences)
In this paper, we use the auxiliary principle technique in conjunction with the Bregman function to suggest and analyze a three-step predictor-corrector method for solving mixed quasi variational-like inequalities. We also study the convergence criteria of this new method under some mild conditions. As special cases, we obtain various new and known methods for solving variational inequalities and related optimization problems.